Anion-assisted Fe(III)-coordination supramolecular systems based on 2, 6-diacetylpyridine dihydrazone. (15th March 2022) - Danilescu, Olga; Bulhac, Ion; Bourosh, Paulina N.; Croitor, Lilia
Graphical abstract: The role of three inorganic anions in the construction of supramolecular structures of Fe(III) 2, 6-diacetylpyridine dihydrazones is reported and discussed. Abstract: Six new iron coordination complexes were obtained as a result of the direct interaction of the Fe 3+ ion and Schiff base ligands in the presence of anions with weak, moderate and high coordinating ability in order to study their role in the construction of diverse supramolecular assemblies. All the crystalline solids present mononuclear complexes: [Fe(H2 L 1 )(H2 O)1.5 (MeOH)0.5 ](ClO4 )3 ·1.75H2 O (1 ), [Fe(H2 L 2 )(H2 O)2 ](ClO4 )3 ·H2 O (2 ), [Fe(HL 1 )(NCS)2 ]·0.25H2 O (3 ), [Fe(HL 2 )(NCS)2 ]·2.33H2 O (4 ), [Fe(L 1 )(N3 )(H2 O)]·H2 O (5 ) and [Fe(L 2 )(H2 O)2 ]OH·4H2 O (6 ), where H2 L 1 = 2, 6-diacetylpyridine bis(isonicotinoylhydrazone) and H2 L 2 = 2, 6-diacetylpyridine bis(nicotinoylhydrazone), which were characterized by IR spectroscopy and single crystal X-ray diffraction. The Schiff base ligands in the perchlorate-assisted compounds adopt a double zwitterion tautomeric form and these coordinate as neutral ligands. In the isothiocyanate complexes, the Schiff base coordinates as a single zwitterionic monoprotonated ligand, while the presence of the N3 – anion in the reaction leads to the bisdeprotonation of both 2, 6-diacetylpyridine dihydrazones. The crystal structures of all the coordination compounds show different types of weak intermolecular interactions, which were confirmed by the analysis of their Hirshfeld surfaces and the corresponding fingerprint diagrams.